Failure Mechanism of Bolts and Countermeasures in Swelling Soft Rock Support - Zhibiao Guo; Lei Zhang; Haohao Wang; Songyang Yin; Tao Li; Xiaohui Kuai (Tehnički Vjesnik, 2018)
The effect of conventional bolt support is not ideal due to the large deformation character of soft rock. As an innovative bolt, constant resistance large deformation (CRLD) bolt has been successfully applied to swelling soft rock engineering, but the reinforcement mechanism is not yet clear. To investigate the interaction mechanism between bolt and surrounding rock, Nanshan Coal Mine of China was selected as the engineering background. The plastic zone of surrounding rock mass and the axial force of three bolts were obtained by theoretical analysis and FLAC3D numerical simulation. Failure processes of conventional pretension bolts in soft rock were reproduced, and the interaction between CRLD bolt and soft rock was investigated in comparison. The results indicate that: (1) The fracture zone of surrounding rock exceeds the anchorage range of the low pretension bolt, the bolt slides with surrounding rock and finally fails. (2) The fracture zone of surrounding rock does not exceed the anchorage range of the high pretension bolt. However, with the accumulation of deformation energy, stress concentration makes the bolt break. (3) CRLD bolt can effectively absorb the deformation energy released by soft rock and maintain constant support resistance. The conclusions obtained in this study provide significant references in the selection of bolts in soft rock engineering.